FIFA World Cup 2022: What can we learn from the inspiring Tokyo 2020 Olympic Games held in COVID-19 times? - Dergaa, I.; Musa, S.; Romdhani, M.; Souissi, A.; Abdulmalik, M.; Chamari, K.; Saad, H. B. (Biology of Sport, 2022)
Preparation for the FIFA World Cup 2022 (WC2022) comes in the time of the COVID-19 pandemic. This study aims were to (i) provide a brief overview of the 2020 Tokyo Olympic and Paralympic games in the context of the COVID-19 pandemic, and (ii) highlight the potential challenges and opportunities central to the hosting of the FIFA WC2022. The organisation, public health policies and prevention protocols of the postponed 2020 Olympic/Paralympic Games (Tokyo July-August 2021), the infection rates during the event, as well as the upcoming WC2022 and its related preparations and challenges, were analysed. An unparalleled International Olympic Committee (IOC) effort, together with the Japanese government and people`s perseverance and drive, enabled the safe delivery of the Tokyo Olympic/Paralympic Games, which left a legacy beyond sport. This has been aided by the collection of critical data and lessons learnt throughout the games. The stringent public health policies and especially the tight bubble system for players and their respective delegations have certainly been the key components that ensured the successful containment of COVID-19 within the targeted population. One of the most significant lessons learned from the Tokyo 2020 Olympics is the improvement made in controlling COVID-19 in the context of mass gathering events. Strict infection control strategies to prevent future COVID-19 transmission during the FIFA World Cup 2022 are an immediate priority in Qatar and are constantly being prepared. The planned measures and health care strategies appear to be well adjusted to the risk, especially for the large anticipated number of visitors, and can provide sufficient guarantees to conduct relatively "safe" mega sports events.